1996
DOI: 10.1093/infdis/174.6.1352
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Colonization in Southern Israel with Antibiotic-Resistant Pneumococci during the First 2 Years of Life: Relation to Serotypes Likely to Be Included in Pneumococcal Conjugate Vaccines

Abstract: Nasopharyngeal carriage of Streptococcus pneumoniae was studied in 162 healthy infants at ages 2, 4, 6, 7, 12, and 13 months and in an additional 352 healthy children at ages 12, 15, 18, 21, and 24 months. Carriage was 26%, 39%, and 62% at 2, 12, and 24 months, respectively, and the respective resistance to > or = 1 antibiotic was 11%, 19%, and 27%. The presence of an older sibling or antibiotic treatment during the month preceding the culture was associated with carriage of resistant pneumococci in infants, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
84
1
14

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(112 citation statements)
references
References 13 publications
13
84
1
14
Order By: Relevance
“…It has been suggested that high rates of antibiotic use may eradicate carriage of pneumococci from most children, but may select for resistant strains when these are present [35]. It is generally considered that there is a high rate of prescription of antibiotics in Hong Kong [23,36].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that high rates of antibiotic use may eradicate carriage of pneumococci from most children, but may select for resistant strains when these are present [35]. It is generally considered that there is a high rate of prescription of antibiotics in Hong Kong [23,36].…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] A number of studies have demonstrated a strong association between daycare attendance and increased carriage of S. pneumoniae, especially of resistant strains. 13,28,29 Study findings demonstrated that daycare attendance and patterns of antibiotic use may be important factors influencing the epidemiology of antibiotic-resistant bacteria.…”
Section: Discussionmentioning
confidence: 95%
“…28,29 Thus, the frequent use of antimicrobial agents to treat upper respiratory infections, a common illness in children in daycare centers, and the close contact of large numbers of young children that commonly occurs in daycare settings, could facilitate the emergence of antibiotic-resistant bacteria. In our study, most of the courses of antibiotics for these children (68/79) were prescribed during the winter time (December-January).…”
Section: Discussionmentioning
confidence: 99%
“…También se mantuvieron cuando se analizó el efecto de haber recibido una pauta vacunal completa. Estos resultados indican que la efectividad de la VNC7v puede ser escasa en circunstancias como las que se observan en Navarra y son consistentes con los de la vigilancia epidemiológica de la ENI 79,127 .…”
Section: Estudios Que Evalúan La Efectividad De La Vnc7vunclassified
“…A diferencia de la vacuna polisacárida, a las vacunas conjugadas antineumocócicas se les atribuye un efecto importante en la reducción de la colonización nasofaríngea por aquellos serotipos presentes en la vacuna 127 . Los hermanos menores de niños que asisten a guarderías tienen un riesgo elevado de ser portadores del neumococo, pero la vacunación de los niños que asisten a guarderías reduce la colonización en sus hermanos [127][128][129] .…”
Section: Inmunidad De Grupounclassified